The multi-RF photon transition driven by strong RF field in optical magnetic resonance of atoms. (January 2022) - Sun, Yujie; Xu, Yunfei; Wang, Zhaoying
Highlights: Multiple RF photon resonance transition is observed with strong RF couple regime. Based on the Flquet perturbation theory, the analytical expression for multi-RF photon resonance frequency is presented. Numerical simulation based on Liouville equation reproduces the experimental features. Abstract: The multiple radio frequency (RF) photon transitions of optical magnetic resonance of 133 Cs atoms are demonstrated theoretically and experimentally. In the presence of a static magnetic field with a fixed direction, the atomic resonance absorption signals irradiated by a circularly polarized light are observed under the condition of different intensities and directions of RF field in our experiment. We find that both the RF intensity and direction can modify the character of the observed signals. If the RF intensity is strong enough, when the RF field is perpendicular to the static magnetic field, only odd number RF photon resonance transitions can be observed. When the RF field is parallel to the static field, no resonance occurs in the experiment. However, if it is between the two cases, all positive integer resonance transitions will be recorded completely. Furthermore, both the analytical solution based on Floquet perturbation theory and the numerical simulation based on Liouville equation strongly support the experimental results. These phenomena enable us to reveal the optical magnetic resonance dynamics more deeply.